3D FEM analysis, dynamic modeling, and performance assessment of transverse flux PMSG for small‐scale gearless wind energy conversion systems. (15th October 2015) - Behjat, Vahid; Amroony Boushehry, Mohammad Javad
Summary: The transverse flux permanent magnet synchronous generator has a great potential for use in direct‐drive wind energy conversion systems due to its large pole numbers, high torque, and power density. This research work develops dynamic model of a single‐side transverse flux permanent magnet synchronous generator for use in a small‐scale gearless wind energy conversion system. For acquiring the parameters of the considered generator, required for dynamic modeling, 3D finite element model of the machine is developed and analyzed in both magneto‐static and transient modes. Field‐oriented control approach is employed for tracking maximum power point from the variable wind speed. The simulation results illustrate an accurate response of the system to the wind speed variation and proper performance of the developed dynamic model and control approach of the system. Copyright © 2015 John Wiley & Sons, Ltd.